PENGARUH ZEOLIT DALAM PUPUK TERHADAP PERTUMBUHAN DAN PRODUKSI PADI SAWAH DI KABUPATEN BADUNG PROVINSI BALI - jufri, akhmad; Rosjidi, Mochamad (Jurnal Sains dan Teknologi Indonesia, 2012)
Many efforts are conducted to increase the fertilising efficiency, especially nitrogen in rice cultivation practices. This field experiment was conducted to evaluate the effect of zeolite on growth and production of lowland rice during rainy season in Badung, Bali. The experiment showed that fertilizer mixed with zeolite resulted in the same growth and productivity, although the fertilising doses was reduced. This means that zeolite incread fertilising efficiency in rice cultivation.